2002
DOI: 10.1016/s1097-2765(02)00784-0
|View full text |Cite
|
Sign up to set email alerts
|

CAND1 Binds to Unneddylated CUL1 and Regulates the Formation of SCF Ubiquitin E3 Ligase Complex

Abstract: The SCF ubiquitin E3 ligase regulates ubiquitin-dependent proteolysis of many regulatory proteins such as p27(Kip1), IkappaB, and beta-catenin. We report the isolation of a CUL1 binding protein, p120(CAND1). We found the majority of CUL1 is in a complex with CAND1 and ROC1 independent of SKP1 and F box protein SKP2. Both in vivo and in vitro, CAND1 prevents the binding of SKP1 and SKP2 to CUL1 while dissociation of CAND1 from CUL1 promotes the reverse reaction. Neddylation of CUL1 or the presence of SKP1 and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
303
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(321 citation statements)
references
References 22 publications
16
303
2
Order By: Relevance
“…32 Interaction between Cul1 and p120 CAND1 is required for SCF function, 33 but p120 CAND1 binds only to unneddylated Cul1. 11,34 For this reason, proper levels of neddylation may be important for SCF function.…”
Section: Discussionmentioning
confidence: 99%
“…32 Interaction between Cul1 and p120 CAND1 is required for SCF function, 33 but p120 CAND1 binds only to unneddylated Cul1. 11,34 For this reason, proper levels of neddylation may be important for SCF function.…”
Section: Discussionmentioning
confidence: 99%
“…Deneddylated cullins can displace the Skp1 and F-box proteins. Once the Nedd8 is displaced, Cand1 comes and binds to the complex thereby rendering the SCF complex inactive (Zheng et al, 2002). Through the yeast hybrid system, it was found that the binding part of MIF was JAB1/CSN5 (Kleemann et al, 2000).…”
Section: Mif and Cell Cyclementioning
confidence: 99%
“…Cullin is a family of scaffold proteins that are involved in various E3 ubiquitin ligases such as the SCF (ROC1-SKP1-cullin1/Cdc53-F box protein) complex; it has been reported that CAND1 may function as a negative regulator of SCF complex assembly. 19,20 As cullin-based ubiquitin ligases have important physiological roles such as cell cycle regulation and cell proliferation, we hypothesized that CAND1 expression would be regulated by miR-148a and that this mechanism would facilitate prostate cancer progression. We investigated whether CAND1 mRNA levels would change by transfecting miR-148a precursor in LNCaP cells (Figure 3a).…”
Section: Mir-148a Regulates Cand1 Expression In Lncap Cellsmentioning
confidence: 99%